Case report: the impact of a resubmission intervention on level 1 distance learning students. (2nd September 2017) - Pinchbeck, Jessica; Heaney, Caroline
ABSTRACT: Student retention and success are key performance indicators within higher education. One of the key opportunities to address both of these lies with the support offered to students who fail a module but are entitled to resubmit. This study investigates the value of implementing a resubmission intervention to improve the quantity and quality of student resubmissions on a level 1 distance learning module. The intervention consisted of an online synchronous tutorial session and a supporting asynchronous forum. The effectiveness of the intervention was measured by comparing the resubmission and pass rates to a previous presentation with no intervention. It was found that resubmission and pass rates were higher where the intervention was used suggesting that a resubmission intervention can increase the quality and quantity of submissions. Whilst, these findings are useful, it is important to acknowledge that there are additional factors that can impact the quantity and quality of resubmissions.